Expression of miRNA-210 in human bone marrow-derived mesenchymal stromal cells under oxygen deprivation - Lončarić, Darija; Stanković, Biljana; Ghousein, Amani; Vreća, Miša; Spasovski, Vesna; Villacreces, Arnaud; Debeissat, Christelle; Grosset, Christophe; Ivanović, Zoran; Pavlović, Sonja (Archives of Biological Sciences, 2019)
Paper description: Cultivation of human bone marrow derived mesenchymal stromal cells (hBM MStroC) expanded at oxygen deprivation conditions increases their efficiency in tissue regeneration. We report a significant increase in miRNA-210 expression during prolonged hBM MStroC expansion at oxygen deprivation, and the involvement of hypoxia-inducible factors 1 and 2 (HIF-1 and HIF-2) in miRNA-210 expression regulation. This is the first study on the expression of miRNA-210 in extended exposure of hBM MStroC to oxygen deprivation, indicating miRNA-210 as a good candidate for a hypoxia-mimicking approach in stem cell therapy. Abstract: A major limitation in the development of efficient clinical protocols for mesenchymal stromal cell (MStroC)-based tissue regeneration therapy is the low retention and survival of MStroC in injured tissue after therapeutic administration. Low oxygen concentration preconditioning(LOP) during ex vivo cultivation of MStroC, as a method for mimicking oxygenation in their physiological microenvironment, has been shown to be beneficial in clinical trials using MStroC. Introducing hypoxia-mimicking molecules into MStroC during cultivation could be an advantageous LOP strategy. MicroRNA (miRNA) drugs are good candidates for this approach. Analysis of the expression of miRNA-210 in human bone marrow-derived MStroC in conditions of acute and extended hypoxia (24 to 72 h) was performed using RT-qPCR methodology. HIF-1α and HIF-2α gene knockdown cell lines were generated using lentiviral transduction of short hairpin RNA (shRNA) in order to examine whether miRNA-210 expression is regulated by transcription factor HIF-1 and/or HIF-2. We detected a significant increase in miRNA-210 expression in hypoxic conditions at time points of 24, 48 and 72 h (p˂0.05). Knocking down of HIF-1α and HIF-2α genes indicated involvement of both transcription factors in the elevation of miRNA-210 expression. These results point to miRNA-210 as a good candidate for a hypoxia-mimicking molecule in LOP strategy. https://doi.org/10.2298/ABS181117001L Received: November 17, 2018; Revised: January 6, 2019; Accepted: January 8, 2019; Published online: January 14, 2019 How to cite this article: Lončarić D, Stanković B, Ghousein A, Vreća M, Spasovski V, Villacreces A, Debeissat C, Grosset CF, Ivanović Z, Pavlović S. Expression of miRNA-210 in human bone marrow-derived mesenchymal stromal cells under oxygen deprivation. Arch Biol Sci. 2019;71(2):201-8.